Hubungan antara Intensitas Penggunaan Smartphone dengan Quality of Life pada Mahasiswa di Semarang - Nurul Azzahrah; Wigyo Susanto; Dwi Heppy Rochmawati (Journal of Health, Medical, and Psychological Studies, 2026)
The development of information and communication technology has led to an increase in smartphone use among students. Smartphones are used not only to support academic activities but also for entertainment and social communication. High smartphone usage can impact various aspects of student life, including quality of life, encompassing physical, psychological, social, and environmental dimensions. This study used a quantitative design with a cross-sectional approach. The sample consisted of 100 undergraduate students of the Nursing Study Program, Faculty of Nursing, UNISSULA, selected using a stratified random sampling technique. The research instruments used were the Smartphone Addiction Scale–Short Version (SAS-SV) and the WHOQOL-BREF. Data analysis was performed using the Spearman Rank correlation test. The results showed that the majority of respondents had a high smartphone usage intensity (63%) and a good quality of life (62%). The Spearman Rank test showed a p-value of 0.000 (<0.05) with a correlation coefficient of r = 0.751, indicating a significant relationship with a strong correlation between smartphone usage intensity and students' quality of life. The conclusion of this study indicates a relationship between the intensity of smartphone use and quality of life in college students